2017
DOI: 10.4172/2476-2067.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Jellyfish Envenomation with Skin and Cardiovascular Manifestations and Treatments

Abstract: Jellyfish are smooth-formed animals in the phylum cnidaria, living in around coastal water zones worldwide. Interacting with jellyfish tentacles, even the beached and dying jellyfish, can prompt millions of nematocysts to perforate the skin and infuse the venom through the inverted long spiny tubules, thereby causing toxic manifestations from no effect to extreme pain to death. According to the structure of nematocyst, quantitative toxins are released into body in a short time. Stung by jellyfish possesses a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 104 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Transcriptomic and proteomic investigations of scyphozoan jellyfish venom revealed that metalloproteinase plays a major role in pathogenesis [16][17][18][19]. It is believed to be the major reason for pain, swelling, and other symptoms associated with jellyfish envenomation [16,20,21]. Further investigation is necessary to completely comprehend the intricate mechanisms of jellyfish venom and to provide efficient treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic and proteomic investigations of scyphozoan jellyfish venom revealed that metalloproteinase plays a major role in pathogenesis [16][17][18][19]. It is believed to be the major reason for pain, swelling, and other symptoms associated with jellyfish envenomation [16,20,21]. Further investigation is necessary to completely comprehend the intricate mechanisms of jellyfish venom and to provide efficient treatments.…”
Section: Introductionmentioning
confidence: 99%